Pendampingan Penyusunan RPP Satu Lembar Bagi Guru Di Wilayah Sidoarjo Dan Surabaya - Purwantiningsih, Budi; M. Amin, M. Amin; Ghozali, Solchan; Alfiyah, Hanik Yuni; Mala, Asnal; Sumawan, Dani (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2021)
The administrative burden arising from the preparation of the RPP is often a complaint of the teacher, not to mention the teacher's task in educating and teaching in the classroom which must also be prepared before teaching, therefore with the assistance of the preparation of the RPP 1 sheet is expected to be able to provide a solution in lightening the burden on the teacher without leaving the elements needed in learning. Based on the monitoring results, the partner schools of Elementary Surabaya want to cooperate in organizing the training activities. The method used is lecture and combined with Focus Group Discussion (FGD) with the following steps: 1) Planning, 2) Implementation, and 3) Evaluation. The results of the service showed that there was success at the preparation and debriefing stage as well as FGD, 100% of subjects were able to identify the components included in the making of the lesson plans, at the demonstration and practice stages, 80% of subjects succeeded and succeeded in making and developing RPP 1 sheet correctly.